Construction of Antecedent Factor Model of Customer Value-Based Loyalty - Irwan Christanto Edy (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: Construction of Antecedent Factor Model of Customer Value-Based Loyalty. The study aims to test the conceptual model of the effect of customer value on customer loyalty through satisfaction, after sales service, trust the brand and relationship marketing. This study is a survey research. The data used are primary that motorcycles customers in the city of Surakarta, as research objects. Data collection instruments in the form of a list of questions (questionnaire) either the open or closed questions. Data analysis methods used include analysis instrument test, descriptive statistical analysis, and analysis of the SEM. The conceptual model that describes the relationship of the value of customer loyalty through satisfaction, after sales service, trust the brand and relationship marketing empirically acceptable (meets the criteria Goodness of fit) scientific. This study found that the value of the customer and after-sales services contribute direct and significant to customer loyalty Keywords: customer value, loyalty, relationship marketingAbstrak: Konstruksi Model Faktor Anteseden Loyalitas Berbasis Nilai Pelanggan. Tujuan Penelitian ini adalah menguji model konseptual pengaruh nilai pelanggan terhadap loyalitas melalui kepuasan, pelayanan purna jual, kepercayaan pada merk dan pemasaran relasional. Penelitian ini merupakan penelitian survai. Data yang digunakan adalah data primer dengan mengambil nasabah sebagai objek penelitian. Instrumen pengumpulan data berupa daftar pertanyaan (kuesioner) baik dengan pertanyaan terbuka maupun tertutup. Metode analisis data yang digunakan meliputi analisis uji instrumen, analisis statistik deskriptif, dan analisis SEM. Model konseptual yang menggambarkan hubungan nilai pelanggan terhadap loyalitas melalui kepuasan, pelayanan purna jual, kepercayaan pada merk dan pemasaran relasional dapat diterima secara empiris. Penelitian ini menemukan bahwa nilai pelanggan dan layanan purna jual memberi kontribusi langsung yang signifikan terhadap loyalitas pelanggan. Kata Kunci: nilai pelanggan, loyalitas, pemasaran relasional